2017
DOI: 10.1108/rpj-02-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

On the use of high viscosity polymers in the fused filament fabrication process

Abstract: Purpose This work aims to provide additional insights regarding the practicability of using conventional materials in the fused filament fabrication (FFF) process. Design/methodology/approach Two different acrylonitryle butadiene styrene (ABS) grades are studied and compared, aiming to check to what extent the regular ABS developed for conventional polymer processing, with a different rheology than the one provided for the FFF process, can also be used in this process (FFF). Findings The rheological result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 20 publications
(29 reference statements)
1
31
0
Order By: Relevance
“…The higher viscosity of PLA3 required higher temperature to achieve the smooth flow necessary for 3D printing. Such an effect of viscosity has been observed in a study by Khaliq and his coworkers when they studied the rheological properties of polymers and their effect on 3D printing . It was found that the more viscous material resulted in poor coalescence and adhesion between the printed materials, which then negatively affected the mechanical properties of the printed products.…”
Section: Resultssupporting
confidence: 77%
“…The higher viscosity of PLA3 required higher temperature to achieve the smooth flow necessary for 3D printing. Such an effect of viscosity has been observed in a study by Khaliq and his coworkers when they studied the rheological properties of polymers and their effect on 3D printing . It was found that the more viscous material resulted in poor coalescence and adhesion between the printed materials, which then negatively affected the mechanical properties of the printed products.…”
Section: Resultssupporting
confidence: 77%
“…The theory of Lagrange multipliers is employed, to derive the continuous adjoint equations, and an augmented cost functional (Lagrangian) is constructed, with the constraints provided by Equations (5) and (7). For the optimization problem (Equation 1), the Lagrangian is given by…”
Section: Dual (Adjoint) Problemmentioning
confidence: 99%
“…While simulations of complex flows with increasing degree of confidence is of great importance, the ability to extract relevant optimization and control strategies dedicated to improving their performance and efficiency is as crucial. Access to such optimization strategies would have vast implications in many areas such as coating, crop protection, inkjet printing, and energy conversion devices [5,6]. From an environmental perspective, taking the example of energy conversion devices, the existence of such capabilities will have a large impact on reducing pollutants/emissions (NOx, soot, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in the era of the rapid development of industry, manufacturing a physical model with complex geometry is not as difficult as it was a few years ago. The computer numerical controlled (CNC) machining, rapid prototyping (RP) and molding techniques have become indispensable branches of industry, allowing for almost any geometry to be manufactured [ 1 , 2 , 3 , 4 ]. They are used within the automotive [ 5 , 6 ], aviation [ 3 , 7 ] and medical industries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The casting patterns can be also made directly with 3D printing methods [ 35 , 36 ] from waxes or from other materials easily removable from the ceramic mold [ 4 , 37 , 38 , 39 ]. Taking into account industrial practice, such a solution does not always work well with the use of standard technological procedures.…”
Section: Introductionmentioning
confidence: 99%